2021
DOI: 10.17305/bjbms.2021.6436
|View full text |Cite
|
Sign up to set email alerts
|

Attributes of intestinal microbiota composition and their correlation with clinical primary nonresponse to anti-TNF-α agents in inflammatory bowel disease patients

Abstract: The largest microbial aggregation in the human body exists in the gastrointestinal tract. The microbiota in the host gastrointestinal tract comprises a diverse ecosystem, and the intestinal microbiota plays a vital role in maintaining gut homeostasis. This study aims to examine whether the gut microbiota influences unresponsiveness to anti-TNF-α treatments in primary nonresponder patients, and consequently identify the responsible microbes as biomarkers of unresponsiveness. Stool samples were collected from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Estevinho et al ( 35 ) observed a lower abundance of Escherichia coli and a higher abundance of SCFA-producing bacteria in anti-TNF therapy responders than in nonresponders. Likewise, a prior study ( 36 ) demonstrated that anti-TNF therapy nonresponders exhibited a reduction in biodiversity and SCFA-producing bacteria. Our study indicated a higher phylum-level abundance of Verrucomicrobiota in patients with remission than in the nonremission group.…”
Section: Discussionmentioning
confidence: 82%
“…Estevinho et al ( 35 ) observed a lower abundance of Escherichia coli and a higher abundance of SCFA-producing bacteria in anti-TNF therapy responders than in nonresponders. Likewise, a prior study ( 36 ) demonstrated that anti-TNF therapy nonresponders exhibited a reduction in biodiversity and SCFA-producing bacteria. Our study indicated a higher phylum-level abundance of Verrucomicrobiota in patients with remission than in the nonremission group.…”
Section: Discussionmentioning
confidence: 82%
“…A comparison of fecal samples from the ADA-responsive and ADA-nonresponsive groups shows that the gut microbiota structure of the responsive group is clearly modified during the treatment period. In detail, protective bacterial genera such as Barnesiella , Anaerostipes , Tyzzerella , Lachnoclostridium , and Lachnospiraceae were found increased in the ADA-responsive samples , while pathogenic bacterial taxa such as Escherichia–Shigella genera were diminished contrarily ( Zhuang et al, 2020 ; Alatawi et al, 2021 ; Mo et al, 2021 ; Chen et al, 2022 ). Such modifications have been reported to reverse the disturbance of the microecosystem, produce more short-chain fatty acids, and correct immunity imbalance ( Cho et al, 2012 ; Meehan and Beiko, 2014 ), indicating that these bacteria may serve as potential microbiota biomarkers for predicting ADA treatment responses.…”
Section: Discussionmentioning
confidence: 91%
“…Dysgonomonas and Butyricicoccus were considered to be potential probiotic bacteria [34,35]. Roseburia and Ruminococcus could produce short chain fatty acids [36,37]. The short chain fatty acids were fermented by some gut microbiota and played an important role in gut health [38].…”
Section: Discussionmentioning
confidence: 99%